Siesta - Gibson, Ginger Foglesong (Greenwillow Books, 2005)
A brother and sister and their teddy bear go through the house gathering items they will need for their siesta in the back yard. A blue backpack. Una mochila azul. Empty! A brother and sister, un hermano y una hermana, and their little bear, un osito. Sleepy! But there are so many things to gather -- and so much to be done! Come join the fun -- in English and Spanish -- and make an ordinary afternoon extraordinary.